2(4-4n)=-6+6n

Simple and best practice solution for 2(4-4n)=-6+6n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4-4n)=-6+6n equation:


Simplifying
2(4 + -4n) = -6 + 6n
(4 * 2 + -4n * 2) = -6 + 6n
(8 + -8n) = -6 + 6n

Solving
8 + -8n = -6 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
8 + -8n + -6n = -6 + 6n + -6n

Combine like terms: -8n + -6n = -14n
8 + -14n = -6 + 6n + -6n

Combine like terms: 6n + -6n = 0
8 + -14n = -6 + 0
8 + -14n = -6

Add '-8' to each side of the equation.
8 + -8 + -14n = -6 + -8

Combine like terms: 8 + -8 = 0
0 + -14n = -6 + -8
-14n = -6 + -8

Combine like terms: -6 + -8 = -14
-14n = -14

Divide each side by '-14'.
n = 1

Simplifying
n = 1

See similar equations:

| 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 | | 10=-16x^2+46 | | x/(1-x)=1.44 | | F(x)=x^100-1 | | 2m=11-3m | | r^3+3r-10=0 | | 6x^2+3x-c=0 | | lg*(x-2)+lg*(x+3)=lg*14 | | (x+3i)(y-2i)=18+6i | | 11r+1=5r+19 | | 6m-12=2m+8 | | 5y-27=3y-5 | | x^2+(k-2)x+(k+3)=0 | | (7+w)(5w-2)=0 | | 2e^2x-3=4equation | | 5x^2-29x-9= | | 80=4x+2y | | -0.5x^2+36x-310=0 | | 0.5x^2+36x-310=0 | | 8-4w=2w+5 | | =3-6x-3x^2 | | 3(6x-6)=-144 | | G(x)=60-3-2x | | 4(10-x)=24 | | G(x)=60-2x | | 8(x+3)=6(x-7) | | H(x)=60+6 | | Cosz+2=0 | | 10ab-5bc=2.5 |

Equations solver categories